Emergence of extensive drug resistance and high prevalence of multidrug resistance among clinical Proteus mirabilis isolates in Egypt - Maggi ElTaweel; Heba Shehta Said; Rasha Barwa (BMC, 2024)
Abstract Background Proteus mirabilis is an opportunistic pathogen that has been held responsible for numerous nosocomial and community-acquired infections which are difficult to be controlled because of its diverse antimicrobial resistance mechanisms. Methods Antimicrobial susceptibility patterns of P. mirabilis isolates collected from different clinical sources in Mansoura University Hospitals, Egypt was determined. Moreover, the underlying resistance mechanisms and genetic relatedness between isolates were investigated. Results Antimicrobial susceptibility testing indicated elevated levels of resistance to different classes of antimicrobials among the tested P. mirabilis clinical isolates (n = 66). ERIC-PCR showed great diversity among the tested isolates. Six isolates (9.1%) were XDR while all the remaining isolates were MDR. ESBLs and AmpCs were detected in 57.6% and 21.2% of the isolates, respectively, where bla TEM, bla SHV, bla CTX−M, bla CIT−M and bla AmpC were detected. Carbapenemases and MBLs were detected in 10.6 and 9.1% of the isolates, respectively, where bla OXA−48 and bla NDM−1 genes were detected. Quinolone resistant isolates (75.8%) harbored acc(6')-Ib-cr, qnrD, qnrA, and qnrS genes. Resistance to aminoglycosides, trimethoprim-sulfamethoxazole and chloramphenicol exceeded 80%. Fosfomycin was the most active drug against the tested isolates as only 22.7% were resistant. Class I or II integrons were detected in 86.4% of the isolates. Among class I integron positive isolates, four different gene cassette arrays (dfrA17- aadA5, aadB-aadA2, aadA2-lnuF, and dfrA14-arr-3-bla OXA−10-aadA15) and two gene cassettes (dfrA7 and aadA1) were detected. While class II integron positive isolates carried four different gene cassette arrays (dfrA1-sat1-aadA1, estXVr-sat2-aadA1, lnuF- dfrA1-aadA1, and dfrA1-sat2). Conclusion P. Mirabilis ability to acquire resistance determinants via integrons may be held responsible for the elevated rates of antimicrobial resistance and emergence of XDR or even PDR strains limiting the available therapeutic options for management of infections caused by those strains.